INCREASE OF ENVIRONMENTAL SAFETY OF MANUFACTURES OF BUILDING MATERIALS WITH REDUCTION OF EMISSIONS OF ASPIRATION BY DUST COLLECTOR WITH FILTERING-FLUIDIZED BED - Sergey Arcadievich Koshkarev; Kirill Sergeevich Koshkarev (Современная наука и инновации, 2022)
The article is devoted to the issue of improving environmental safety by reducing the aspiration emissions by the filter - fluidized bed dust collectors with an insignificant degree of breakthrough of trapped dust particles of aspiration schemes at construction industry. It was presented description’ approach for drying in bulk building materials and capturing of aspiration’ dust emissions for evaluation of the degree particles’ leakage throughout proposed fluidized bed dust collectors.